Efeito do polimento com diferentes técnicas sobre o brilho e rugosidade superficial de resinas compostas - Lippert, Vinícius Funghetto (2021)
Objective: This study aimed to evaluate the effect of three different polishing systems on the roughness and surface gloss of composite resins for direct use. Methods: Three different composite resin systems were selected: nano-hybrid (Harmonize, Kerr); nano-filled (Z350 XT, 3M ESPE) and supra-nanometric (Estelite Omega, Tokuyama). Ninety samples, thirty for each composite resin, with 6 mm in diameter and 8 mm in height were made. After the initial polymerization process, the samples were treated with #320 sandpaper. Subsequently, all samples went through a finishing process with a 12-blade multilaminated drill (Jota AG) and the 30 samples from each group were subdivided into three different polishing systems (n = 10) with rubbers from one (OneGloss, Shofu) , two (EVE Diacomp Twist Basic CA, EVE) and three (Astropol, Ivoclar Vivadent) steps. In addition, after polishing, all samples went through a simulated toothbrushing process for one year. Roughness (Ra) assessments with a rugosimeter (SJ 201, Mitutoyo) and AFM (Dimension Icon PT, Bruker Nano Inc) and surface gloss (Novo-Curve, Rhopoint Instruments) were evaluated at all stages. The Analysis of variance (ANOVA) for repeated measures was performed, considering effects of interaction between resin and time, and between resin, polisher and time. Correlations were made using the Spearman coefficient (rs). A significance level of 5% (P=0.05) was considered. Results: There were statistically significant differences over the 4 moments for all variables (P <0.001). However, the Ra measured by the rugosimeter and the gloss did not have differences between T2 and T3 (P = 0.999 and P = 0.900 respectively). For Ra with the rugosimeter between resins over time, a significant interaction effect was found on time*resin (P <0.001). Likewise, it was found for Ra with AFM (P <0.001) and for brightness (P <0.001). It was possible to observe through the Spearman correlation coefficient (rs) between the roughness (measured by the rugosimeter and the AFM) and the gloss, that the correlations are statistically significant (P <0.001), from moderate to strong and inverse, in all of the resins and separating by type of resin. The qualitative analyzes of AFM were in agreement with the quantitative results. Conclusion: It is essential to carry out the finishing and polishing procedures for composite resin restorations in an appropriate manner to obtain the ideal surface roughness and gloss. Two- and three-step systems with diamond particles still seem to be the best option for polishing, regardless of the type and composition of inorganic particles in the resin system.